A Case of Nasal Glial Heterotopia in an Adult - Akira Hagiwara; Noriko Nagai; Yasuo Ogawa; Mamoru Suzuki (Case Reports in Otolaryngology)
We report a rare case of nasal glial heterotopia in an adult. After the surgery, frontal lobe cerebral hemorrhage developed. A 58-year-old man had unilateral nasal obstruction that progressed for one year. He had been treated for hypertension, chronic heart failure, and cerebral infarction with aspirin and warfarin. A computed tomography scan showed that the tumor occupied the right nasal cavity and the sinuses with small defect in the cribriform plate. The tumor was removed totally with endoscopy. After the operation, the patient developed convulsions and frontal lobe cerebral hemorrhage. The hemorrhage site was located near a defect in the cribriform plate. Nasal glial heterotopia is a rare developmental abnormality, particularly rare in adult. Only few cases were reported. We could not find any report of adult nasal glial heterotopias that developed cerebral hemorrhage as a complication of the surgery.